2015
DOI: 10.1007/s11095-015-1731-1
|View full text |Cite
|
Sign up to set email alerts
|

A Uniform Ultra-Small Microsphere/SAIB Hybrid Depot with Low Burst Release for Long-Term Continuous Drug Release

Abstract: These results demonstrate the potential application of a uniform ultra-small microsphere/SAIB hybrid depot for continuously delivering small drug molecules for long periods of time without burst release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Lin et al. (2015) demonstrated that combining PLGA microspheres with SAIB depots could reduce the burst release of risperidone to 0.64% after 1 day.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al. (2015) demonstrated that combining PLGA microspheres with SAIB depots could reduce the burst release of risperidone to 0.64% after 1 day.…”
Section: Introductionmentioning
confidence: 99%
“…No obvious burst release was observed in formulations S1, S2, and S4 (cumulative release of RM was only 5% in the first 24 h), indicating that drug escape was effectively prevented by the dual-controlled system combining in situ gel with RM-MS. During the formation of the semisolid implant, drug release was strongly inhibited by the controlled release effect of the PLGA MS, which contributed to a low drug diffusion rate from MS into the in-situ gel. Only a small amount of drug derived from the MS surface would be released into the medium during this lag time (Lin et al., 2015 ). Formulations S3 and S5 had a low burst release (13% and 24%, respectively), while formulation S6 exhibited a high initial burst (48%).…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al. ( 2015 ) developed a uniform ultra-small microsphere/sucrose acetate isobutyrate (SAIB) hybrid depot to provide a long-term sustained release system for the water-insoluble drug, Risperidone; it not only reduced the burst release of the SAIB depot, but also eliminated the lag-time of the PLGA microspheres. It is worth considering that most existing clinical medications are hydrophilic small-molecule compounds, and compared to that of water-insoluble drugs, the quick and unstable drug release profiles make it tougher for controlled release of water-soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The suspensions are known to cause slower absorption than solutions and result in a zero order drug absorption profile (35). In addition, as the time elapsed, the biodegradation of sucrose acetate isobutyrate must also have begun and after four days of administration would slowly have started contributing to the enhancement in drug release from gel depot matrix (36).…”
Section: Discussionmentioning
confidence: 99%